2023
DOI: 10.1007/s10980-023-01645-7
|View full text |Cite
|
Sign up to set email alerts
|

Prerequisites for coexistence: human pressure and refuge habitat availability shape continental-scale habitat use patterns of a large carnivore

Abstract: Context Adjustments in habitat use by large carnivores can be a key factor facilitating their coexistence with people in shared landscapes. Landscape composition might be a key factor determining how large carnivores can adapt to occurring alongside humans, yet broad-scale analyses investigating adjustments of habitat use across large gradients of human pressure and landscape composition are lacking. Objectives Here, we investigate adjustments in habitat u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 73 publications
2
10
0
Order By: Relevance
“…adjustments of habitat use with varying habitat availability also termed functional responses; Aarts et al, 2013), whereas spatial proximity alone is often a poor proxy of model transferability (Yates et al, 2018). Our results thus indicate that functional responses might be a main factor explaining variation in habitat selection by lynx across Europe, which is well in line with recent results highlighting adjustments by lynx across gradients of human pressure and landscape composition (Oeser et al, 2023). While previous studies have highlighted the usefulness of including predictor variables at multiple scales for capturing functional responses (Aldossari et al, 2022;Matthiopoulos et al, 2011;Paton & Matthiopoulos, 2016), as in our global environment approach, our comparison showed that combining habitat maps from local models can also achieve good performance.…”
Section: Discussionsupporting
confidence: 88%
“…adjustments of habitat use with varying habitat availability also termed functional responses; Aarts et al, 2013), whereas spatial proximity alone is often a poor proxy of model transferability (Yates et al, 2018). Our results thus indicate that functional responses might be a main factor explaining variation in habitat selection by lynx across Europe, which is well in line with recent results highlighting adjustments by lynx across gradients of human pressure and landscape composition (Oeser et al, 2023). While previous studies have highlighted the usefulness of including predictor variables at multiple scales for capturing functional responses (Aldossari et al, 2022;Matthiopoulos et al, 2011;Paton & Matthiopoulos, 2016), as in our global environment approach, our comparison showed that combining habitat maps from local models can also achieve good performance.…”
Section: Discussionsupporting
confidence: 88%
“…Community‐based conservation organizations already practice sub‐diurnal conflict mitigation strategies, such as enhanced livestock guarding between dusk and dawn when lions move closer to agro‐pastoral areas (Oriol‐Cotterill, Macdonald, et al, 2015). These practices could be expanded to increase the availability of vegetative patches that act as spatiotemporal refuge within a landscape of fear (Palmer et al, 2022), thereby reprieving lions from daytime anthropogenic risk (sensu Oeser et al, 2023; Schuette et al, 2013). Increased vegetative cover could also bolster lion hunting success, potentially enhancing prey accessibility at night and lessening the need to consume livestock.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the exact placement of our arrays in the wider landscape may mean the MCPs did not always enclose the most probable areas to detect lynx because the wetlands, rivers and landscape heterogeneity within the array may push the activity centre clusters away from the centre of arrays. To overcome these aspects in future surveys, we recommend using habitat suitability maps (Oeser et al., 2023), simulating different sampling designs (Ash et al., 2020) or employing pre‐season surveys to inform camera trap placements.…”
Section: Discussionmentioning
confidence: 99%
“…Suitable habitat for lynx in Europe's fragmented landscapes is constrained by human disturbance, which lynx avoid (Oeser et al., 2023; Ripari et al., 2022). Reintroduced lynx populations in Central Europe also exhibit genome‐wide diversity loss, requiring the immediate need to increase connectivity between populations (Mueller et al., 2022; Papp et al., 2020; Premier et al., 2021).…”
Section: Discussionmentioning
confidence: 99%